Advances in Lectin Microarray Technology: Optimized Protocols for Piezoelectric Print Conditions. Issue 1 (March 2013) - Pilobello, Kanoelani T.; Agrawal, Praveen; Rouse, Richard; Mahal, Lara K.
Abstract: Lectin microarray technology has been used to profile the glycosylation of a multitude of biological and clinical samples, leading to new clinical biomarkers and advances in glycobiology. Lectin microarrays, which include >90 plant lectins, recombinant lectins, and selected antibodies, are used to profile N ‐linked, O ‐linked, and glycolipid glycans. The specificity and depth of glycan profiling depends upon the carbohydrate‐binding proteins arrayed. The current set targets mammalian carbohydrates including fucose, high mannose, branched and complex N ‐linked, α‐ and β‐galactose and GalNAc, α‐2, 3‐ and α‐2, 6‐sialic acid, LacNAc, and Lewis X epitopes. Previous protocols have described the use of a contact microarray printer for lectin microarray production. Here, an updated protocol that uses a non‐contact, piezoelectric printer, which leads to increased lectin activity on the array, is presented. Optimization of print and sample hybridization conditions and methods of analysis are discussed. Curr. Protoc. Chem. Biol. 5:1‐23 © 2013 by John Wiley & Sons, Inc.